One man a committee does not make: Henry Manne, the AEA-AALS joint committee, and the struggle to institutionalize law and economics - David Gindis; Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2022)
In 1965, Henry Manne convinced the Association of American Law Schools and the American Economic Association to establish an ad hoc Joint Committee to explore the possibilities of collaborative efforts between economists and legal scholars. This paper examines the origins and activities of this Joint Committee and reveals that its work was far less about promoting increased interaction between economists and legal scholars than about a conscious attempt to use this committee to help fashion a particular form of law and economics that would reshape legal analysis in a way consistent with Manne's vision. Though the Committee's effective life was very short and its direct influence negligible, the lessons learned informed Manne's subsequent efforts to institutionalize law and economics within the legal academy.
Keywords: B20; B30; K00; K13; K20; 330; Law and economics; Henry Manne; American Economic Association; Association of American Law Schools; products liability; George Stigler; Roland McKean